Analysis of Vocational Graduates Absorption in the Digital Printing Industry through Alumni Tracking: A Case Study of Multimedia Students at VHS 1 Trenggalek, Indonesia - Effrila Dianitasari; Yoto Yoto; Nunung Nurjanah (Belantika Pendidikan, 2022)
This study aims to analyze the absorption of the workforce of SMK graduates from the multimedia expertise program who work in digital printing either as employees or opening their own businesses. This research was conducted in the city of Trenggalek with the target of SMK Negeri 1 Trenggalek. The technique of collecting data is with documentation techniques from documents and data from the school's Special Employment Exchange (BKK) report. Qualitative descriptive analysis technique, where qualitative data is presented in the form of descriptive descriptions, tables, charts or pictures to facilitate the presentation of information. The results showed that multimedia graduates from 2016/2019 to 2018/2019 who were absorbed in the digital printing industry continued to increase. The decline in job absorption in the digital printing industry experienced a decline in graduates in 2019/2020 possibly due to the impact of Covid19.